The Influence of Application Quality, Promotion, and Brand Awareness Regarding the Decision to Download the Cash Application - Daniel, Desmon; Fathorrahman, Fathorrahman; Pradiani, Theresia (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The high level of digitalization drives changes in people's behavior in accessing information. The widespread access to the internet in Indonesia has had a significant impact on the existence of mainstream media, especially print media in Indonesia. The challenge of digital transformation is the hope of print media to be able to maintain revenue amidst the decline in newspaper print circulation. Kontan as one of the print media in Indonesia is also not immune from digital transformation and media convergence by launching the Kontan Application as a super app for Kontan news. The presence of the Kontan Application is expected to increase the number of readers and revenue of Kontan in the long term. This study aims to prove and analyze the influenceApplication Quality, Promotion and Brand awareness towards the decision to download the Kontan application either partially or simultaneously. This type of research is quantitative research with primary data sources through questionnaires as the data collection method.The population in this study was 979 Kontan application customers who had subscribed for at least 1 month.Sampling using probability sampling technique with the following types:simple random sampling,The research sample was taken as many as 100 customers. The questionnaire in this study used a 5-point Likert scale, was created using surveymonkey.com, and distributed online via email blast. The data analysis technique used multiple linear regression and hypothesis testing used the t-test and F-test. The conclusion that can be drawn in this study is thatApplication quality has a positive and significant effect on the decision to download. While the variables Promotion and Brand awarenesshas no effect on the decision to download.Application Quality, Promotion and Brand awareness simultaneously influence the decision to download.